Fluid challenge and balloon occlusion testing in patients with atrial septal defects. Issue 11 (19th August 2021) - D'Alto, Michele; Constantine, Andrew; Chessa, Massimo; Santoro, Giuseppe; Gaio, Gianpiero; Giordano, Mario; Romeo, Emanuele; Argiento, Paola; Wacker, Julie; D'Aiello, Angelo Fabio; Sarubbi, Berardo; Russo, Maria Giovanna; et al.
Abstract : Introduction: Careful, stepwise assessment is required in all patients with atrial septal defect (ASD) to exclude pulmonary vascular or left ventricular (LV) disease. Fluid challenge and balloon occlusion may unmask LV disease and post-capillary pulmonary hypertension, but their role in the evaluation of patients with 'operable' ASDs is not well established. Methods: We conducted a prospective study in three Italian specialist centres between 2018 and 2020. Patients selected for percutaneous ASD closure underwent assessment at baseline and after fluid challenge, balloon occlusion and both. Results: Fifty patients (46 (38.2, 57.8) years, 72% female) were included. All had a shunt fraction >1.5, pulmonary vascular resistance (PVR) <5 Wood Units (WU) and pulmonary arterial wedge pressure (PAWP) <15 mm Hg. Individuals with a PVR ≥2 WU at baseline (higher PVR group) were older, more symptomatic, with a higher baseline systemic vascular resistance (SVR) than the lower PVR group (all p<0.0001). Individuals with a higher PVR experienced smaller increases in pulmonary blood flow following fluid challenge (0.3 (0.1, 0.5) vs 2.0 (1.5, 2.8) L/min, p<0.0001). Balloon occlusion led to a more marked fall in SVR (p<0.0001) and a larger increase in systemic blood flow (p=0.024) in the higher PVR group. No difference was observed in PAWP following fluid challenge and/or balloon occlusion between groups; four (8%) patients reached a PAWP ≥18 mm Hg following the addition of fluid challenge to balloon occlusion testing. Conclusions: In adults with ASD without overt LV disease, even small rises in PVR may have significant implications on cardiovascular haemodynamics. Fluid challenge may provide additional information to balloon occlusion in this setting.